The sleep of Behemoth disputing peace and violence in medieval Europe, 1000/1200 - Malegam, Jehangir Yezdi 1976- (Ithaca Cornell University Press, 2013)
Millennial reform and revisions of peace -- The papal reform : peace espoused and repudiated -- False sacraments : violence, captivity and insurrection -- Dueling sacraments : the communion of Judas Iscariot -- Mediations between self and society : peace, discretion and discipline -- Peacemaking, ecclesiology and evangelism -- Communes : inversions of peace -- Disciplining Behemoth : provisions for secular peace
Includes bibliographical references and index
Online-Ausg.
In English
Keywords: To 1500; Peace -- Religious aspects -- Catholic Church -- History -- To 1500; Christianity and politics -- Catholic Church -- History -- To 1500; Violence -- Religious aspects -- Catholic Church -- History -- To 1500; Christianity and politics -- Europe -- History -- To 1500; HISTORY - Medieval; RELIGION - Christian Life - Social Issues; RELIGION - Christianity - General; Christianity and politics; Christianity and politics - Catholic Church; Peace - Religious aspects - Catholic Church; Violence - Religious aspects - Catholic Church; Church History; History; Europe -- Church history -- 600-1500; Europe - Histoire religieuse - 476-1492; Europe